2022
DOI: 10.13168/agg.2022.0008
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical approach for the ancient iron in Sungai Batu, Bujang Valley, Kedah, Malaysia

Abstract: Archaeological evidence has demonstrated that the Bujang Valley is Malaysia's richest archaeological site and served as the primary coastal centre. A study in the Bujang Valley found monuments related to trading activities and others that functioned as a temple related to the Hindu-Buddhist period. The main purpose of this study was to resolve issues and problems arising from previous studies related to the Bujang Valley civilisation, particularly in terms of iron studies. Geophysics plays a vital role in assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The study of Mokhtar (2019;2012) and Muztaza (2015) at the Sungai Batu and Jeniang archeological sites did not record any findings of bellow used in iron smelting activities in the area. For the bellow production experiment, the reference from the study of Bandama (2010) has been used as a yardstick related to the shape of the wind pump used in iron smelting activities in Africa.…”
Section: Bellow Experiments Makingmentioning
confidence: 75%
See 4 more Smart Citations
“…The study of Mokhtar (2019;2012) and Muztaza (2015) at the Sungai Batu and Jeniang archeological sites did not record any findings of bellow used in iron smelting activities in the area. For the bellow production experiment, the reference from the study of Bandama (2010) has been used as a yardstick related to the shape of the wind pump used in iron smelting activities in Africa.…”
Section: Bellow Experiments Makingmentioning
confidence: 75%
“…Mokhtar (2019) The use of raw materials from the riverbanks of the ancient Sungai Batu was proposed based on XRF, XRD and SEM analysis of the samples which revealed the similarity of the elements and mineral content of both the furnace and soil samples. XRD analysis has revealed the presence of quartz, phyllites and soil minerals (muscovite, montmorillonite and illite) which are also reinforced by SEM analysis which clearly shows the presence of subsidual and subcircular quartz which explains the raw material taken in river environment (Mokhtar, 2019). XRF analysis also showed that the silica and alumina content dominated the sample between 62.94% and 10.33-15.54% which explains the use of raw materials in the area around Sungai Batu as the raw materials for furnace manufacturing.…”
Section: Sb2hmentioning
confidence: 83%
See 3 more Smart Citations